Analisis Keberlanjutan Lingkungan dalam Pengembangan Sektor Pariwisata: Perspektif Ekonomi Lingkungan di Destinasi Wisata - Andrisman Satria (Samudra Publisher, 2023)
The sustainable development paradigm has become the main focus in overcoming the negative impact of the tourism sector on the environment. There is increasing debate about how the development of the tourism sector should be directed so that it continues to provide economic benefits without harming the environment which is the main attraction of tourist destinations. This study aims to find out how the integration of environmental economic aspects in the planning and management of tourist destinations can help achieve environmental sustainability goals and, what are the concrete strategies that can be implemented to maximize the economic benefits of the tourism sector, while maintaining a balance with environmental sustainability in tourist destinations. The research method used in this research is this research uses a qualitative approach to analyze environmental sustainability in the development of the tourism sector. Data was collected through in-depth interviews with various stakeholders involved in the development of the tourism sector in tourist destinations in Aceh Singkil. The qualitative data obtained from the interviews will be analyzed using a content analysis approach. Interview transcripts will be broken down thematically to identify patterns, trends and key aspects related to the analysis of environmental sustainability and environmental economics in the development of the tourism sector. This research reveals that the integration of environmental economic aspects in the planning and management of tourist destinations plays a crucial role in achieving environmental sustainability goals. The research results show that an approach that combines economic and environmental factors in tourism development can create a positive synergy that benefits both aspects. The results of this study reveal several concrete strategies that can be implemented to maximize the economic benefits of the tourism sector, while maintaining a balance with environmental sustainability in tourist destinations. First, the integration of environmental economic models in tourism development planning has proven to be an effective approach.